Film art : an introduction - Bordwell, David; Thompson, Kristin, 1950-; Smith, Jeff, 1962 December 17- (New York McGraw Hill, 2020)
"Film Art provides the respected scholarship and analytic tools students need to understand key vocabulary and concepts of film forms, techniques, and history;appreciate a wide variety of classic and contemporary films and the creative choices made by filmmakers to shape the experience of viewers; and analyze films critically and systematically to enrich their understanding and appreciation of any film, in any genre"--
Film as art: creativity, technology, and business -- The significance of film form -- Narrative form -- The shot: mise-en-scene -- The shot: cinematography -- The relation of shot to shot: editing -- Sound in the cinema -- Summary: style and film form -- Film genres -- Documentary, experimental, and animated films -- Film criticism: sample analyses -- Historical changes in film art: conventions and choices, tradition and trends.
Includes bibliographical references and index.
Keywords: Motion pictures -- Aesthetics